A Search for Exoplanets around Northern Circumpolar Stars. VIII. Filtering Out a Planet Cycle from the Multi-Period Radial Velocity Variations in M Giant HD 36384 - Byeong-Cheol Lee; Gwanghui Jeong; Jae-Rim Koo; Beomdu Lim; Myeong-Gu Park; Tae-Yang Bang; Yeon-Ho Ch; Hyeong-Ill Oh; Inwoo Han (Journal of the Korean Astronomical Society, 56(2), 2023)
This paper is written as a follow-up observations to reinterpret the radial velocity (RV) of HD 36384, where the existence of planetary systems is known to be ambiguous. In giants, it is, in general, difficult to distinguish the signals of planetary companions from those of stellar activities. Thus, known exoplanetary giant hosts are relatively rare. We, for many years, have obtained RV data in evolved stars using the high-resolution, fiber-fed Bohyunsan Observatory Echelle Spectrograph (BOES) at the Bohyunsan Optical Astronomy Observatory (BOAO). Here, we report the results of RV variations in the M giant HD 36384. We have found two significant periods of 586 d and 490 d. Considering the orbital stability, it is impossible to have two planets at so close orbits. To determine the nature of the RV variability variations, we analyze the HIPPARCOS photometric data, some indicators of stellar activities, and line profiles. A significant period of 580 d was revealed in the HIPPARCOS photometry. H𝛼 EW variations also show a meaningful period of 582 d. Thus, the period of 586 d may be closely related to the rotational modulations and/or stellar pulsations. On the other hand, the other significant period of 490 d is interpreted as the result of the orbiting companion. Our orbital fit suggests that the companion was a planetary mass of 6.6 𝑀J and is located at 1.3 AU from the host.